2016
DOI: 10.1007/978-1-4939-3271-9_30
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy for the Treatment of Neurological Disorders: Metabolic Disorders

Abstract: Metabolic disorders comprise a large group of heterogeneous diseases ranging from very prevalent diseases such as diabetes mellitus to rare genetic disorders like Canavan Disease. Whether either of these diseases is amendable by gene therapy depends to a large degree on the knowledge of their pathomechanism, availability of the therapeutic gene, vector selection, and availability of suitable animal models. In this book chapter, we review three metabolic disorders of the central nervous system (CNS; Canavan Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 173 publications
(231 reference statements)
0
23
0
Order By: Relevance
“…Pools of these osmolytes are primarily located in glia and are directly involved in the regulation of water homeostasis, membrane stability, pH and survival [ 8 , 14 , 16 , 21 , 23 , 34 ]. NAA distribution is dynamically regulated during osmotic fluctuations, but the role of NAA as osmolyte remains controversial [ 6 , 8 , 18 , 30 , 64 , 72 , 74 , 76 ]. Importantly, our findings indicate that increased NAA concentrations are uncoupled from CNS pathology and neurological dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pools of these osmolytes are primarily located in glia and are directly involved in the regulation of water homeostasis, membrane stability, pH and survival [ 8 , 14 , 16 , 21 , 23 , 34 ]. NAA distribution is dynamically regulated during osmotic fluctuations, but the role of NAA as osmolyte remains controversial [ 6 , 8 , 18 , 30 , 64 , 72 , 74 , 76 ]. Importantly, our findings indicate that increased NAA concentrations are uncoupled from CNS pathology and neurological dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…CD is a bona fide target for gene therapy as it is a devastating, fatal childhood disorder and there is no treatment available. In the mouse, a naturally short-lived mammalian species, systemic AAV-mediated ASPA delivery has recently shown great therapeutic success [ 2 , 30 ]. Nevertheless, immunogenicity and limitations in production continue to impede systemic AAV delivery for treatment of CNS disorders in humans [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gene therapy for NDDs represents a rapidly developing novel therapeutic approach with a potential capability of restoring normal neuronal functions [37] by intracellular delivery of exogenous genetic material, carrying a disease correcting/therapeutic information in the form of recombinant deoxyribonucleic acid (DNA) or ribonucleic acid (RNA) molecules engineered into a delivery vehicle, known as vector. Once inside a recipient (host) cell, the transferred genetic material utilizes cellular machinery to biosynthesize (translate the encoded information into) therapeutic proteins aimed at replacing their defective counterparts, produced in neurons by mutated endogenous gene, inactivating the mutated gene's product or inserting a foreign transgene with therapeutic properties to battle the disease.…”
Section: Choosing An Ideal Vectormentioning
confidence: 99%
“…Although most gene therapies involve local administration or ex vivo gene transfer ( Table 1 ), the advent of Zolgensma confirmed that in vivo targeted gene therapy is a clear possibility and is expected to further accelerate the development of DDS technology in anticipation of gene therapy. In addition, gene therapy has emerged as having potential for the treatment of CNS diseases in the past decade [ 11 , 12 , 13 , 14 , 15 ]. Gene therapy strategies and therapeutic effects for CNS diseases that have been demonstrated are summarized in Table 2 .…”
Section: Introductionmentioning
confidence: 99%